Keefektifan Penggunaan E-Learning Berbasis Google Docs Terhadap Hasil Belajar Mahasiswa Pada Mata Kuliah Teknologi Informasi Di Stikes Siti Hajar - Ida Aryani Pasaribu; Sulaiman Sulaiman; Ronal Erwansyah (LPPM Sekolah Tinggi Ilmu Kesehatan Siti Hajar Medan, 2019)
Abstract Background: This study aims to analyze and describe the effectiveness and activeness of students in the use of Google Docs-based E-Learning in learning on learning outcomes in the Information and Communication Technology courses at the Siti Hajar STIKes Method: This research used experimental research design with pretest-posttest group random control pattern, wherein this design a group of subjects was taken into the experimental group and the control group. with the Physiotherapy Student 2017/2018 Learning Year population. The data analysis method used in this study is descriptive analysis, preliminary data analysis, and final data analysis Conclusion: The application of Google Docs-based E-Learning has proven to be effective and increases student activity and learning outcomes. It can be seen from the increasing percentage of students' activeness from the medium to high category and the improvement in student learning outcomes from the quite good categories.